An advanced blind-tube monitoring instrument to improve the characterization of subsurface radioactive plumes - Elísio Soraia (EDP Sciences, 2021)
This research presents a design of a resilient blind-tube radiometric logging probe, which satisfies key, operational site constraints, for direct in-situ characterization of subsurface radioactivity, particularly caesium-137 and strontium-90. The probe comprises a commercially-available Ø10 mm × 9.5 mm CeBr3 scintillator detector attached to a compact digitizer unit, in a resistant and waterproof housing. The probe is designed to be lowered down into metallic Ø 75 mm blind-tubes by means of a winch system.